Analisis Faktor-faktor yang Mempengaruhi Kepuasan Debitor Kredit Konsumtif di Bank BNI Cabang Probolinggo - Sukrispiyanto, Sukrispiyanto (Jurnal Aplikasi Manajemen, 2008)
Target of company is beside to obtain:get optimal advantage of its business activity, also try to fulfill requirement and desire of consumer: This research to test factors influencing satisfaction of client. factors influencing satisfaction of client in this research is performance of product of core of idiosyncrasy of addition, reliability, service of servicebility) and quality which is perception (perceived of quality). This research is conducted by in Sub-Province of Probolinggo by taking case al Bank of BNI Branch Probolinggo. Population of this research is all consumptive credit debitor client in Bank of BNI Branch Probolinggo a number of 1100 people. From amount of population, is later, then determined by size measure of sample counted 92 people, with consideration that amount of the sampel have the including big sampel. Sampling technique the used is sampling random simple. As for Technique analyzer the used is analysis of regresi. Pursuant to result of analysis and also examination of hypothesis which is can be pulled by conclusion that Perception of client about product performance of core of in the form of assessment of satisfaction of client to physical facility exist in BNI Branch Probolinggo, having score mean 3,83. Perception of client about idiosyncrasy of addition have score mean 3,60. Perception of client about reliability have score mean 3.41. Perception of client aboul service have score mean 4.11. Perception of client about quality of which is perception have score mean 3,69. the Score mean show good perception. From result of examination of hypothesis can be concluded that: Performance variable (performance) of product of core of, idiosyncrasy of addition features), reliability, service (quality and servicebility) which is perception (perceived of quality) having an effect on by simultan 10 satisfaction of consumptive credit debitor client in Bank of BNI Branch Probolinggo. Variable Performance product of core of having influence by signifikan to variable satisfaction of client. Variable idiosyncrasy of addition have influence by signifikan to variable satisfaction of reliability nasabah. Variabel have influence by signifikan lo variable satisfaction of client. Service variable have influence by signifikan to variable satisfaction of nasabah. Variabel of quality of which is perception have influence by signifikan to variable satisfaction of client. From some variable, what most having an effect on to satisfaction of client is variable of quality of which is perception